CAD/CAE associative features for cyclic fluid control effect modeling. Issue 2 (3rd March 2016) - Li, Lei; Ma, Yongsheng
Abstract: Nowadays, CAE has been widely applied in industry as an auxiliary tool for decision making. However, human intervention still is required in reasoning CAE results and in determining design change effect. Ideally, CAD and CAE should be seamlessly integrated where design changes, effect analysis and function reasoning should be explicitly supported by automatic feature extraction in a cyclic manner. This paper presents two CAD/CAE associative feature concepts, which form a robust mechanism aiming to support automatic CAD/CAE interactions with both geometric and semantic information. Firstly, a concept of CAE boundary feature is proposed to model and record the simulation intents, and therefore, the CAE analysis cycles could be managed with the consistent initialization setups, e.g. boundary conditions, mesh types, and physical models. Secondly, CAE results are processed by extracting the differential characteristic features, which are named as CAE effect features . An effective feature reflects the sensitivity information related to each engineering change and hence leads to the evaluation of design modifications. Consequently, the cyclic design modifications can be tracked and reasoned; then further modifications are guided to converge into the optimum. The research innovation lies in the proposed CAD/CAE integration scheme which has been explored preliminarily to demonstrate an automated and efficient way to keep the CAD/CAE semantic consistency over cycles of optimization. A case study about hydraulic valve development is presented. GRAPHICAL ABSTRACT: